2010
DOI: 10.1007/978-3-642-14400-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agent Based Clustering: Towards Generic Multi-Agent Data Mining

Abstract: Abstract.A framework for Multi Agent Data Mining (MADM) is described. The framework comprises a collection of agents cooperating to address given data mining tasks. The fundamental concept underpinning the framework is that it should support generic data mining. The vision is that of a system that grows in an organic manner. The central issue to facilitating this growth is the communication medium required to support agent interaction. This issue is partly addressed by the nature of the proposed architecture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These findings are currently being incorporated into a MAS framework [6,7]. The techniques investigated sofar, and reported here, do not serve to find the best results in all cases and further investigation is therefore required, however the authors are greatly encouraged by the result reported in this paper.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…These findings are currently being incorporated into a MAS framework [6,7]. The techniques investigated sofar, and reported here, do not serve to find the best results in all cases and further investigation is therefore required, however the authors are greatly encouraged by the result reported in this paper.…”
mentioning
confidence: 87%
“…The process was incorporated into a MAC framework founded on earlier work by the authors and reported in [6,7]. An issue with K-means is that the initial points (records/objects) used to define the initial centroids of the clusters are randomly selected.…”
Section: Parameter Identification For Clustering Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This offers advantages where it is not easy or not possible for data to be first collated; for example, because of security and privacy preserving issues or because of technical issues. MADM also supports the creation of frameworks that can be allowed to grow in an almost anarchic manner, additional agents can be easily incorporated into such frameworks as long as they comply with whatever protocols have been specified [2,11]. However, the true power of agents is their ability to behave in an autonomous manner and interact (negotiate) in order to provide a solution to a problem.…”
Section: Introductionmentioning
confidence: 97%
“…Clustering results are available at anytime and are continuously revised to achieve the global clustering. Previous work by the authors [11] investigated a MABC mechanism founded on the framework presented in [2], however this could be more accurately be described as a distributed clustering system founded on an agent architecture so that the benefits of this architecture (ready to use communication channels, etc.) could be adopted.…”
Section: Introductionmentioning
confidence: 99%